Nutritional supplement use by elite young UK athletes: fallacies of advice regarding efficacy - Petroczi, A.; Naughton, D. P.; Pearce, G.; Bailey, R.; Bloodworth, A.; McNamee, M. J. (Journal of the International Society of Sports Nutrition, 2008)
The objective was to study nutritional supplement use among young elite UK athletes to establish whether a rationale versus practice incongruence exists, and to investigate the sources of information. Survey data were analysed for association between supplements used and motives for using such substances among young athletes along with the sources of advice and literature precedents on supplement effects.